Complete mitochondrial genome sequence of Pulveroboletus ravenelii (Boletales, Basidiomycota). Issue 9 (2nd September 2022) - Cho, Sung-Eun; Kwag, Young-Nam; Han, Sang-Kuk; Lee, Dong-Hyeon; Kim, Chang Sun
Abstract: Pulveroboletus ravenelii, an ectomycorrhizal fungus, has long been used in traditional Chinese medicine and mushroom dyes; however, its mitogenome and phylogenetic relationship with other taxa remain unexplored. Here, we sequenced the mitochondrial genome of P. ravenelii using next-generation sequencing and found that its mitogenome, a circular DNA molecule of 43, 528 bp, comprised 15 protein-coding genes, 15 transfer RNA genes, and two ribosomal RNA genes. The mitogenome had a base composition of A (37.52%), C (11.14%), G (12.21%), and T (39.13%) and a GC content of 23.35%. A phylogenetic tree was constructed to determine the phylogenetic relationship of this species with other taxa based on the mitochondrial genome sequence. This study revealed the phylogenetic positions of P. ravenelii and its related genera for the first time.